Notes on Norse Finds from the East Coast of Ellesmere Island, N.W.T. - Schledermann, Peter (ARCTIC, 1980)
During the 1978 and 1979 field seasons in the Bache Peninsula region on the east coast of Ellesmere Island . a number of artifacts mostly of European manufacture and presumably related to Norse activities was located in old Thule culture winter house ruins. The finds were made on three sites in the study area . Skraeling Island (Chain mail sections, knife blades, boat rivets, iron point and copper pieces, woolen cloth), the Eskimobyen site on Knud Peninsula (barrel bottom, box section, copper piece), and Haa Island (ivory figurine). A general description of these finds, locational data, associated radiocarbon dates and material analyses are presented. .